THE PROBLEM OF MEDICINES INTERCHANGEABILITY. FOCUS ON PERINDOPRIL - A. I. Malyhina; M. V. Zhuravleva; A. K. Starodubtsev; M. L. Maksimov; O. A. Rogacheva (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To evaluate the therapeutic equivalence between generic perindopril (Parnavel, LLC Ozone, Russia) and the original perindopril (Prestarium A, Laboratories Servier, France). Material and methods. Patients with arterial hypertension, grade 1-2 (n=40, aged 35-75 years) were included into the open randomized cross-over trial. The previous anti- hypertensive therapy was discontinued before study for 14 days in all patients. Each of the patients was randomized for alternate 8-week treatment with the original (Prestarium A) and generic (Parnavel) perindopril. Treatment efficacy was assessed by the achievement of target blood pressure (BP) <140/90 mm Hg. The drug dose was increased in the efficacy lack and inapamide was added if necessary. Therapy was discontinued for 14 days after 8 weeks of treatment with the first randomization drug, and the same therapy course with the other study drug was carried out. Side effects were also recorded.Results. A significant reduction in systolic (SBP) and diastolic BP (DBP) was found in patients of Parnavel group by 28 mm Hg (19%) and 17 mm Hg (19%), respectively. In the patients of Prestarium A group SBP and DBP reduction was 27 mm Hg (18.5%) and 16 mm Hg (18.7%), respectively. After 2 months of therapy the target BP level (<140/90 mm Hg) was achieved in 95% and 90% of patients in Parnavel and Prestarium A groups, respectively. Drug tolerability was comparable.Conclusion. Efficacy and tolerability data demonstrated therapeutic equivalence of generic perindopril (Parnavel) to the original perindopril.